Wpływ japońskich doświadczeń na teorię i praktykę zarządzania zachodnich przedsiębiorstw - Bembenek, Bogusław; Piecuch, Teresa (The influence of Japanese experiences on the theory and practice of the management of western companies, 2009)
Contemporary managers are still fascinated by the Japanese models and methods of company management. This is a result not only of the Japanese concept of creation and achieving harmony in life and work but mainly the result of the considerable effectiveness of these business concepts. This work focuses on the specificity of the Japanese model of management. The emphasis is also put on the creative methods of Japanese origin which allow to solve various problems, as well as on management techniques which have originated in Japan or other countries in the Far East. These methods and techniques have been more and more often successfully implemented in American and European companies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 358-370